Sosialisasi Peningkatan Pemahaman Manajemen Organisasi sebagai Upaya Membangun Generasi Muda yang Berwawasan Organisasi di SMA Negeri 1 Ampel - Fajar Istiqomah; Sri Wahyuni; Anita Rosalia Putri; Galuh Wahyu Lestari; Unna Ria Safitri (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
This outreach program aims to improve students' understanding of organizational management as part of an effort to develop a young generation with organizational insight at SMA Negeri 1 Ampel. The implementation of this outreach program is motivated by the importance of providing students with management concepts, organizational structures, and self-management skills so they can participate actively and effectively in various school organizational activities. The outreach program is delivered through material presentations and the use of interactive media in the form of Kahoot games designed to facilitate students' understanding of management concepts in a more engaging, enjoyable, and easily applicable way. Evaluation is conducted using a questionnaire covering five aspects: understanding of management concepts, awareness of the importance of management in life, effectiveness of interactive media, motivation to become leaders, and the ability to organize and plan for the future. The evaluation results show that this outreach program is able to broaden students' horizons, increase leadership motivation, and help them focus more on designing future goals. Thus, this outreach program is considered effective in supporting the development of a young generation with organizational insight in a sustainable manner.